In the role of Brie Hutchens ... - Melleby, Nicole (Algonquin Young Readers, 2020)
After telling a lie to her mother because she is not ready to come out to her mother as gay, strong-willed eighth grader Brie Hutchens must deal with the consequences in her relationships with her friends, faith, and family.